Fast and efficient Sb-based type-II phototransistors integrated on silicon - Lining Liu; Simone Bianconi; Skyler Wheaton; Nathaniel Coirier; Farah Fahim; Hooman Mohseni (APL Photonics)
Increasing the energy efficiency and reducing the footprint of on-chip photodetectors enable dense optical interconnects for emerging computational and sensing applications. While heterojunction phototransistors (HPTs) exhibit high energy efficiency and negligible excess noise factor, their gain-bandwidth product (GBP) has been inferior to that of avalanche photodiodes at low optical powers. Here, we demonstrate that utilizing type-II energy band alignment in an Sb-based HPT results in six times smaller junction capacitance per unit area and a significantly higher GBP at low optical powers. These type-II HPTs were scaled down to 2 μm in diameter and fully integrated with photonic waveguides on silicon. Thanks to their extremely low dark current and high internal gain, these devices exhibit a GBP similar to the best avalanche devices (∼270 GHz) but with one order of magnitude better energy efficiency. Their energy consumption is about 5 fJ/bit at 3.2 Gbps, with an error rate below 10−9 at −25 dBm optical power at 1550 nm. These features suggest new opportunities for creating highly efficient and compact optical receivers based on phototransistors with type-II band alignment.